Industrial democracy in Europe: a quantitative approach. (2nd April 2020) - Sanz de Miguel, Pablo; Welz, Christian; Caprile, Maria; Rodríguez Contreras, Ricardo
ABSTRACT: Industrial democracy is a dimension of industrial relations which has been largely studied. However, the international comparison of the different features and outcomes of industrial democracy has attracted much less attention. The article addresses this gap by developing three tools: a dashboard of indicators, a composite indicator aiming to measure performance, and a typology addressed to better understanding varieties of national industrial relations system. Whilst industrial democracy performance is defined in a normative way, the typology includes also other aspects related to industrial relations institutions, processes and actors. Both normative and non-normative indicators are included in the dashboard. The three tools allow for cross-time analysis and are seen as complementary for the comparative analysis of industrial democracy in Europe.